Aplicabilidade das tecnologias digitais de informação e comunicação para o ensino de línguas(gens) na prática docente - Riedner, Viviane (2023)
It is, therefore, in the scenario of the covid-19 pandemic that the question raised for the development of this thesis is conducted, whose general objective is to investigate how the implementation of active, collaborative and hybrid methodologies mediated by Digital Information and Communication Technologies (TDICs), in the conduction of pedagogical activities, can contribute to the teaching-learning process of Languages in Professional and Technological, Higher Education (Associates Degree), during the period of social distancing at the Federal Institute of Pará (IFPA), Santarém Campus, locus of the research. The investigation was planned from a single central question, separated into four guiding questions. Therefore, it was asked about the limits and possibilities of applying the TDICs as a didactic pedagogical resource in the face-to-face and remote teaching of Languages in Professional and Technological, Higher Education. The research is based in the area of Applied Linguistics, being qualitative, interpretive with an ethnographic approach, supported by Clifford (2002) and Flick (2009), whose analysis of the material generated through the interview technique in the format of a synchronous online focus group (Murray, 1997; Gondim, 2002), followed the methodology of Content Analysis, in Bardin (2016). For the theoretical foundation, studies by Lévy (2010), Alves (2020), Bortoni-Ricardo (2008), Moita Lopes (2006), Kenski (2013), Zulfa (2021), Hodgers et al. (2020), Moran (2017; 2018; 2019) and other theorists who support publications in scientific repositories Scielo, CAPES journal portal, Scopus and Google Scholar. The content analysis corpus was made up of the experience reports of three (3) teachers and four (4) Language teachers at IFPA, Santarém Campus. At the end of the exploration/analysis phases of reports to achieve specific objectives, I hope that the study of this thesis will stimulate reflections and new research in the area of Languages and other curricular subjects, on the conduct of active methodologies, collaborative and hybrid processes through TDICs, so that teachers can analyze, rethink and (re)construct pedagogical practice in Technical and Technological Education.